2021
DOI: 10.3390/cells10102596
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Chaperone/Co-Chaperone Interactions with Small Molecules: A Novel Approach to Tackle Neurodegenerative Diseases

Abstract: The dysfunction of the proteostasis network is a molecular hallmark of neurodegenerative diseases such as Alzheimer’s disease, Parkinson’s disease, Huntington’s disease, and amyotrophic lateral sclerosis. Molecular chaperones are a major component of the proteostasis network and maintain cellular homeostasis by folding client proteins, assisting with intracellular transport, and interfering with protein aggregation or degradation. Heat shock protein 70 kDa (Hsp70) and 90 kDa (Hsp90) are two of the most importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 164 publications
0
2
0
Order By: Relevance
“…There are other promising small-molecule Hsp90-modulator candidates that have been tested in the context of neurodegenerative disease and heat shock response. One can refer to two excellent recent reviews for details [ 166 , 167 ]. A meta-analysis of the Alzheimer’s disease proteome revealed that the levels of Hsp90 family members is reduced in diseased brains, while most other chaperones and co-chaperones do not show change, with the notable exception of Hsp70, its nucleotide exchange factor BAG3, and neuronal small HSPs, which were found to be upregulated [ 168 ].…”
Section: Hsp90 As a Target In Diseases Of Proteostasismentioning
confidence: 99%
“…There are other promising small-molecule Hsp90-modulator candidates that have been tested in the context of neurodegenerative disease and heat shock response. One can refer to two excellent recent reviews for details [ 166 , 167 ]. A meta-analysis of the Alzheimer’s disease proteome revealed that the levels of Hsp90 family members is reduced in diseased brains, while most other chaperones and co-chaperones do not show change, with the notable exception of Hsp70, its nucleotide exchange factor BAG3, and neuronal small HSPs, which were found to be upregulated [ 168 ].…”
Section: Hsp90 As a Target In Diseases Of Proteostasismentioning
confidence: 99%
“…For the diseases associated with impaired protein folding, influencing the activity of chaperone systems may be one of the targets in drug therapy [53], either by altering chaperone gene activity [54] or by acting on chaperones with the molecules that enhance or weaken their function [55]. These therapeutic strategies are being developed for neurodegenerative diseases, among others [54][55][56][57][58].…”
Section: Chaperone Proteinsmentioning
confidence: 99%